Creating a safe haven for university students: How are we doing? - Sanders, Mark (My University, 2012)
Too frequently and often too late, academic librarians learn of patron experiences involving problem patrons, misdemeanor criminal activity, or poorly secured areas. Regrettably, these experiences can irrevocably diminish perceptions of access to the vibrant learning spaces and services offered by our institutions. This article assesses the current state of security personnel staffing and patron security issues at 25 public, four-year universities in two southeastern states. This is an electronic version of an article published in the Journal of Access Services. The Journal of Access Services is available online at: http://www.tandfonline.com.
Keywords: Access services; Circulation services; Library as place; Library organizational models; Security; Library staffing; Problem patrons; Academic libraries